2011
DOI: 10.1111/j.1365-2664.2010.01951.x
|View full text |Cite
|
Sign up to set email alerts
|

Methods of enhancing botanical diversity within field margins of intensively managed grassland: a 7-year field experiment

Abstract: Summary1. Increased intensification in agricultural grasslands has led to well-documented declines in the associated flora. Manipulation of field margins for biodiversity enhancement in arable systems has been extensively investigated. However, there is a paucity of corresponding long-term research within intensively managed grasslands. 2. We investigated a combination of establishment and management methods to enhance botanical diversity of newly established field margins in intensively managed grasslands. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 41 publications
(45 reference statements)
3
53
0
Order By: Relevance
“…In a study under continuous grazing no change was observed in species richness (Jacquemyn et al, 2011). In contrast, grazing was found to increase (due to light grazing of cattle, Fritch et al, 2011) or decrease (due to overgrazing by horses, Penksza, 2005) the species richness compared to the mowing treatment (Fritch et al, 2011, Penksza, 2005. Mowing found to decrease the abundance of disturbance sensitive species, while increased the disturbance-tolerant ruderal species by frequent destruction of above-ground plant organs (Socher et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a study under continuous grazing no change was observed in species richness (Jacquemyn et al, 2011). In contrast, grazing was found to increase (due to light grazing of cattle, Fritch et al, 2011) or decrease (due to overgrazing by horses, Penksza, 2005) the species richness compared to the mowing treatment (Fritch et al, 2011, Penksza, 2005. Mowing found to decrease the abundance of disturbance sensitive species, while increased the disturbance-tolerant ruderal species by frequent destruction of above-ground plant organs (Socher et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, it is hard to separate the direct effects of species composition change from other related effects (changes of leaf area index, soil bulk density, and soil water holding capacity) on carbon sequestration (Klumpp et al, 2011). Management regime shifts from grazing to mowing could have a significant, but varying (negative vs. positive) effect on species composition (Fritch et al, 2011, Jacquemyn et al, 2011, Socher et al, 2012. In general grasslands mostly benefit from light grazing and mowing and degrade in terms of species composition from frequent mowing and intense grazing but the direction of change also depends on the initial status of the grassland (Jantunen, 2003, Socher et al, 2012.…”
Section: Introductionmentioning
confidence: 99%
“…That work showed that reseeding with a 485 diverse mixture of grass and wildflowers could successfully result in more diverse 486 vegetation in new experimental field margins in dairy systems, and that cessation of 487 fertiliser inputs alone was ineffective in increasing vegetation diversity. More recent 488 research on these same plots confirmed long-term positive effects of the reseeding 489 treatment on plant and invertebrate diversity (Fritch et al 2009(Fritch et al , 2011. A large body of 490 international research suggests that properly managed field margin habitats can be a 491 significant reservoir of farmland wildlife and biodiversity (e.g.…”
mentioning
confidence: 82%
“…Purvis et al (2009a, p. 17-20) Critique of expected effects of REPS 4 on habitats and hoverfly diversity. Included REPS status as a variable in multivariate analysis of habitats on 50 farms (thirteen of which were REPS participants) Field margins Feehan et al (2005) Fritch et al (2009, 2011, Purvis et al (2009a), Sheridan et al (2008Sheridan et al ( , 2009 Finn et al (2007Finn et al ( , 2009 Finn et al (2008b) Kelly (2008) Carlin et al (2010) Multi-criteria analysis used to assess the effectiveness of REPS (and Italian scheme) based on data in the mid-term evaluation only. Experts' ratings of measures in REPS 2.…”
mentioning
confidence: 99%
“…In a sample of European AESs, Primdahl et al (2010) found that biodiversity measures were least likely to have evidence-based models of such causeand-effect relationships. Under AEOS, the management specifications for THM, particularly where sites are relatively species poor, are unlikely to be sufficient to either enhance the species richness or encourage the establishment of positive indicator species (Bakker and Berendse, 1999;Fritch et al, 2011). The latest AES -GLAS (DAFM, 2015) -has introduced a further relaxation of THM management specifications, with permissible nitrogen application rates being increased from 30 (REPS and AEOS) to 40 kg N/ha (GLAS).…”
Section: Targeting and Value For Moneymentioning
confidence: 99%